SUPPLIER SELECTION BASED ON CAPABILITIES INDEX FOR MULTIPLE CHARACTERISTICS WITH ONE SIDED SPECIFICATION - Erik Bagus Prasetyo; Nani Kurniati (SINERGI, 2018)
Raw materials are a significant requirement in the production process for manufacturing companies. In meeting the needs of raw materials for the production process, most manufacturing firms rely on suppliers. Supplier selection is an essential part of manufacturing companies. From several supplier selection criteria, quality is one of the fundamental standards and is used in supplier assessment. Selecting suppliers based on the quality of their products will have a positive impact on manufacturing companies, such as increased profits through reduced operational costs and increased market share. The problem faced is the lack of accuracy in choosing qualified suppliers. In this study will compare two suppliers at manufacturing companies and pick one that has a higher capability value. Supplier selection is made by using multiple characteristic capability indexes. The Supplier will be selected by comparing the ratio of two suppliers. Numerical calculations are performed on leather suppliers in shoe companies based on bursting quality, tear strength, tensile strength and elongation. The result of the calculation can be seen that supplier B is chosen as a better supplier. Characteristics of quality will affect the production process and application of shoes.